2013
DOI: 10.2807/1560-7917.es2013.18.43.20616
|View full text |Cite
|
Sign up to set email alerts
|

Human infection with avian influenza A(H7N9) virus re-emerges in China in winter 2013

Abstract: Through a national surveillance system for unexplained pneumonia, a severe case of influenza A(H7N9) in a man in his mid-30s was identified in Zhejiang Province, China on 14 October 2013. Epidemiological and clinical findings were consistent with the patterns reported during the outbreak in spring 2013, and laboratory findings showed that the virus had 99.6% identity with earlier H7N9 viruses identified in humans in the spring except for five mutations in the NA gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 8 publications
(14 reference statements)
2
56
0
Order By: Relevance
“…However, it is not clear which species of birds are most likely to be infected and are shedding levels of virus sufficient to infect humans. The lack of understanding of the virus ecology in birds has recently resulted in an additional number of human cases, demonstrating that the virus still circulates in China (11). Based on the initial reports of this virus and previous experience with avian influenza, we evaluated the potential role of different poultry species in the epidemiology of H7N9 influenza.…”
mentioning
confidence: 99%
“…However, it is not clear which species of birds are most likely to be infected and are shedding levels of virus sufficient to infect humans. The lack of understanding of the virus ecology in birds has recently resulted in an additional number of human cases, demonstrating that the virus still circulates in China (11). Based on the initial reports of this virus and previous experience with avian influenza, we evaluated the potential role of different poultry species in the epidemiology of H7N9 influenza.…”
mentioning
confidence: 99%
“…Pan et al [22] analyzed the outbreak pattern of H7N9 epidemic empirically, and found that the space-time networks among the connected cities were distributed along the time sequence of the outbreak, which revealed that some areas in eastern China had higher non-uniform distribution risk of Human infections with avian influenza A(H7N9) virus. Chen et al [4] believed that enhanced monitoring of humans and animals could ensure early detection and diagnosis of suspected cases, while the closure of live poultry markets also could reduce the risk of disease. Ai et al [3] used conditional logistic regression factor analysis in cases and control, and found that H7N9 virus infection was significantly related with the live poultry exposure, the chronic medical conditions and related environmental exposure.…”
Section: Research Status Analysesmentioning
confidence: 99%
“…Han et al [13] analyzed the relationship between Human infections with avian influenza A(H7N9) virus in Huzhou city and the exposure of live poultry, and found that there was an obvious epidemiological link between them. In addition, the closure of live poultry markets and the suspension of live poultry trading were effective measures to control the spread of the H7N9 virus in the high-incidence areas, which could significantly reduce the incidence of outbreaks [2], and the live poultry markets infected by H7N9 virus were the most likely source of the epidemic [4,6,10].…”
Section: Research Status Analysesmentioning
confidence: 99%
“…It was reported that 1 L of serosanguineous fluid was drained from his chest upon autopsy. In 2013, another avian IAV emerged in Southeast Asia; this time an H7N9 virus (12,13,141,144). The histopathology was similar to H5N1; severe pneumonia, diffuse alveolar damage, and epithelial necrosis were common features of infection with both viruses (12,13).…”
Section: Continuing Emergence Of Avian Iavmentioning
confidence: 99%
“…The histopathology was similar to H5N1; severe pneumonia, diffuse alveolar damage, and epithelial necrosis were common features of infection with both viruses (12,13). Patients infected with either virus had high levels of CXCL10, CCL2, IL-6, and CXCL8 in the plasma and displayed peripheral blood leukopenia and neutrophilia (10,14,92,141,142,144). There were slightly more bacterial co-infections in cases of H7N9 compared to H5N1 avian IAV (12,13,92).…”
Section: Continuing Emergence Of Avian Iavmentioning
confidence: 99%